2019
DOI: 10.1016/j.ejso.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment and prognosis of breast cancer in elderly – A population-based study

Abstract: Background: The aim of this study was to investigate outcome of treatment in patients over 80 years of age with early breast cancer at the time of the diagnosis with special interest in surgical treatment. Materials and methods: Breast cancer patients older than 80 years of age, treated at the Breast Surgery Unit of Helsinki University Hospital in 2005e2010 were identified from electronic patient records. Patients were followed-up until the end of 2014. Patient and tumour characteristics, recurrences, comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Of the patients who did not receive surgery, 78.4% received chemotherapy. Moreover, survival benefit of surgical treatment in patients older than 80 years have also been confirmed in another study [ 27 ], and surgical treatment was safe in older patients.…”
Section: Discussionmentioning
confidence: 64%
“…Of the patients who did not receive surgery, 78.4% received chemotherapy. Moreover, survival benefit of surgical treatment in patients older than 80 years have also been confirmed in another study [ 27 ], and surgical treatment was safe in older patients.…”
Section: Discussionmentioning
confidence: 64%
“…Of the patients who did not receive surgery, 78.4% received chemotherapy. Moreover, survival bene t of surgical treatment in patients older than 80 years have also been con rmed in another study, (27) and surgical treatment was safe in older patients.…”
Section: Discussionmentioning
confidence: 70%
“…Van de Glas et al showed that the proportion of older BC patients that did not receive breast surgery increased substantially from 9.2% in 1995 to 30.1% in 2011 [17]. Moreover, previous population-based studies showed that the proportion of older BC patients receiving primary endocrine therapy is higher in the Netherlands than in other European countries [22,23,24]. The EUROCARE breast cancer group found lower survival rates in European countries, like England and Ireland, where older BC patients are treated more often with primary endocrine therapy omitted [22].…”
Section: Discussionmentioning
confidence: 99%